Narrativas e Reflexões Críticas sobre a Constituição da Identidade de Professoras Negras nas Escolas da Rede Municipal de Uberlândia - MG - Mendes, Alzira Ribeiro de Sousa (2024)
This master’s research is part of the line of research on Educational Knowledge and Practices of the Postgraduate Program in Education of the Faculty of Education of the Federal University of Uberlandia (PPGED/FACED/UFU) and its object of study is the constitution of the identity of self-declared black teachers, working in Basic Education of municipal public schools in Uberlandia, Minas Gerais (MG), Brazil. The general objective is to investigate the development of the identities of these teachers; therefore, the theoretical references related to ethnic-racial issues were analyzed, as well as the narratives presented by the teachers, regarding life experiences, in order to understand their experiences and challenges. The mobilizing question was: how do the construction and development of the identities of black women responsible for mediating the teaching-learning process of students in municipal public schools of Uberlandia (MG) occur? To achieve the understanding of the object of study, a dialogue was established with the following authors: Flávia Biroli (2018); Vera Maria Candau (2014); bell hooks (2017); Vanessa Therezinha Bueno Campos, Graça Aparecida Cicillini and Fernanda Araújo Silva (2015); Grada Kilomba (2019); Vera Maria Candau and Luiz Fernandes de Oliveira (2010); Luiz Fernandes de Oliveira, Catherine Walsh and Vera Maria Ferrão Candau (2018); Arilda Schimit Godoy (2005); Stuart Hall (2006); Nilma Lino Gomes (1995, 1999, 2002a, 2002b, 2003, 2005a, 2005b, 2008, 2017, 2019); Armando Pivesan and Edméa Rita Temporini (1995), among others. The research is exploratory in nature, with a qualitative approach, since the challenges of everyday school life require the understanding of the contradictions present in the manifestations of the subjects in their perceptions, actions and words. The following criteria were defined to select the study participants: a) self-declared black women; b) effective teachers in the municipal public education system; c) working in Basic Education; d) acceptance to participate in the research as collaborators and respective consent in the Free and Informed Consent Form (FICF). Interviews were the instrument for gathering information, some of which occurred in person and others, virtually. The State of the Question (SQ) and the analysis of the interviews led to an understanding of the process of identity construction of black female teachers, which is different from the way observed with white teachers, in view of the Eurocentric social oppression exercised through racism and sexism, in the sense of making black women invisible and discrediting them, when in leadership positions, while at the same time conditioning them to subordinate roles. It was noted that public education institutions are unprepared to address racial issues and enable students and professionals with stereotypes that differ from what is considered normal to feel a sense of belonging. This indicates the need to change curricula and daily practices to ensure black representation in different contexts, inside and outside the classroom, starting with textbooks and initial and ongoing training. Teachers also have the responsibility to decolonize, renouncing white privileges, by using the community to enhance actions to combat racism. We hope that this research will help people of different ethnic origins to value and understand the importance of black history and ancestry, with a view to mutual and enriching learning.